ELASTISITAS PERMINTAAN TENAGA KERJA DI PROVINSI SULAWESI TENGGARA - Teguh Permana; Puspitaningsih, Andriani; Ariani, Waode Rachmasari; Afiat, Muhammad Nur; Surianti (UNPERBA, 2025)
This study aims to determine the elasticity of labor demand in Southeast Sulawesi Province. This type of research is quantitative research with data sources from BPS. The analysis tool used is the labor demand elasticity formula. The findings of this study are that in 2024 the elasticity of labor demand is elastic, while in 2023 and 2022 it is inelastic. The implication is that the government must be careful in determining policies related to minimum wages because it will act quickly on labor demand.